2020
DOI: 10.7554/elife.55513
|View full text |Cite
|
Sign up to set email alerts
|

Late-life restoration of mitochondrial function reverses cardiac dysfunction in old mice

Abstract: Diastolic dysfunction is a prominent feature of cardiac aging in both mice and humans. We show here that 8-week treatment of old mice with the mitochondrial targeted peptide SS-31 (elamipretide) can substantially reverse this deficit. SS-31 normalized the increase in proton leak and reduced mitochondrial ROS in cardiomyocytes from old mice, accompanied by reduced protein oxidation and a shift towards a more reduced protein thiol redox state in old hearts. Improved diastolic function was concordant with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 70 publications
12
84
1
Order By: Relevance
“…Further, we show that SS-31 treatment preserved mitochondrial function in both cardiac and diaphragm muscle from C26 mice by preserving oxidative phosphorylation and preventing proton leak into the mitochondrial matrix. A similar positive influence of SS-31 on cardiac and skeletal muscle in heart failure was recently shown which implicated mitochondrial bioenergetics and redox signaling in the development of muscle dysfunction [31,32]. This is important because increased proton leak can augment oxidant production within the mitochondrial matrix leading to a disruption of redox balance within the muscle tissue [33,34].…”
Section: Discussionmentioning
confidence: 55%
“…Further, we show that SS-31 treatment preserved mitochondrial function in both cardiac and diaphragm muscle from C26 mice by preserving oxidative phosphorylation and preventing proton leak into the mitochondrial matrix. A similar positive influence of SS-31 on cardiac and skeletal muscle in heart failure was recently shown which implicated mitochondrial bioenergetics and redox signaling in the development of muscle dysfunction [31,32]. This is important because increased proton leak can augment oxidant production within the mitochondrial matrix leading to a disruption of redox balance within the muscle tissue [33,34].…”
Section: Discussionmentioning
confidence: 55%
“…We suggest that the restoration of aged mitochondrial function that is conferred by SS-31 is directly attributable to this effect. However, the resulting enhancement in diastolic function is likely to require downstream changes, as the functional benefit took up to 8 weeks to reach full effect, and required post-translational modifications of contractile protein elements ( Chiao et al, 2020 ). It is increasingly recognized that mitochondrial function, including redox status and energetics, has far-reaching effects, including epigenetic alterations and post-translational modifications ( Olgar et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In aged mice, SS-31 ameliorates kidney glomerulopathy ( Sweetwyne et al, 2017 ) and brain oxidative stress ( Hao et al, 2017 ) and has shown beneficial effects on skeletal muscle performance ( Siegel et al, 2013 ). We have recently shown that administration of SS-31 to 24-month-old mice for 8 weeks reverses the age-related decline in diastolic function, increasing the E/A from just above 1.0 to 1.22, restoring this parameter 35% toward that of young (5-month-old) mice ( Chiao et al, 2020 ). However, how SS-31 benefits and protects aged cardiac cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For quantitative analysis, MASIC was used to extract the reporter ion intensities from the raw data [ 19 ]. An in-house R script was used to link the peptide identifications and quantifications as described before [ 20 ]. Reporter ion intensities for PSMs corresponding to the same unique peptide were summed and log2 transformed.…”
Section: Methodsmentioning
confidence: 99%